Gender differentiated adaptation strategies considering climate risk perceptions, impacts, and socio-technical conditions in Senegal’s Dry Regions - Kumar, Shalander; Pramanik, Soumitra; Yessofou, Adjani Nourou-Dine; Das, Abhishek; Singaraju, Niyati; Puskur, Ranjitha; Gondwe, Therese; Huyer, Sophia (International Crops Research Institute for the Semi-Arid Tropics, 2023)
The present study attempts to understand the farmers’ gender-differentiated perception of climate risk and its impact, access to climate information, and adaptation strategies in Senegal’s dry regions. Study uses data collected from 514 households through primary survey between May and June 2022 covering Kaffrine, Louga and Thies subregions and multiple communes, including 5% women-headed households and 12% women respondents. Preliminary findings show that the perception of men and women on the phenomena of climate risk and its potential impact on farming systems is similar; however, the women’s access to climate information services (CIS) and climate-smart agriculture (CSA) technologies is relatively very low. The women farmers were found to be much more vulnerable to climate risks, but they often rely on traditional coping mechanisms rather than modern CSA technologies. Both men and women emphasized the importance of context-specific climate information. Although 78% households had access to CIS or some kind of training on CSA, among these it was the men in 73% households and only in 5% in households where women had access to CIS or training on CSA. A refocus of current CIS and CSA programs—with a provision of increased frequency and women-preferred timings of CIS through radio broadcasts, and CSA interventions addressing risk in vegetable production and small animals—will make these programs gender responsive. In addition, we propose appropriate institutional interventions that are critical to address cultural barriers by enhancing women’s role in farming decision-making, and access to CIS and CSA.